A Place at the Table: LTD as a Mediator of Memory Genesis. (August 2016) - Connor, Steven A.; Wang, Yu Tian
Resolving how our brains encode information requires an understanding of the cellular processes taking place during memory formation. Since the 1970s, considerable effort has focused on determining the properties and mechanisms underlying long-term potentiation (LTP) at glutamatergic synapses and how these processes influence initiation of new memories. However, accumulating evidence suggests that long-term depression (LTD) of synaptic strength, particularly at glutamatergic synapses, is a bona fide learning and memory mechanism in the mammalian brain. The known range of mechanisms capable of inducing LTD has been extended to those including NMDAR-independent forms, neuromodulator-dependent LTD, synaptic depression following stress, and non-synaptically induced forms. The examples of LTD observed at the hippocampal CA1 synapse to date demonstrate features consistent with LTP, including homo- and heterosynaptic expression, extended duration beyond induction (several hours to weeks), and association with encoding of distinct types of memories. Canonical mechanisms through which synapses undergo LTD include activation of phosphatases, initiation of protein synthesis, and dynamic regulation of presynaptic glutamate release and/or postsynaptic glutamate receptor endocytosis. Here, we will discuss the pre- and postsynaptic changes underlying LTD, recent advances in the identification and characterization of novel mechanisms underlying LTD, and how engagement of these processes constitutes a cellular analog for the genesis of specific types of memories.